2017
DOI: 10.1111/medu.13335
|View full text |Cite
|
Sign up to set email alerts
|

Integrated and implicit: how residents learn CanMEDS roles by participating in practice

Abstract: Context Learning outcomes for residency training are defined in competency frameworks such as the CanMEDS framework, which ultimately aim to better prepare residents for their future tasks. Although residents’ training relies heavily on learning through participation in the workplace under the supervision of a specialist, it remains unclear how the CanMEDS framework informs practice‐based learning and daily interactions between residents and supervisors. Objectives This study aimed to explore how the CanMEDS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…To assess perceived needs, participants were asked to ‘Describe three CPD topic you would like to learn about in the next 12 months’. To identify learning needs that may have arisen from problems encountered in practice, participants were asked to ‘Describe three challenging cases or situations encountered in the past 12 months.’ Given that physicians have varying understanding of the constructs underlying intrinsic competencies[1013], we refrained from asking respondents to describe learning needs and challenges pertaining to these specific competencies. Rather, our aim was to elicit authentic descriptions of learning needs and challenges encountered in practice across a wide range of specialists.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess perceived needs, participants were asked to ‘Describe three CPD topic you would like to learn about in the next 12 months’. To identify learning needs that may have arisen from problems encountered in practice, participants were asked to ‘Describe three challenging cases or situations encountered in the past 12 months.’ Given that physicians have varying understanding of the constructs underlying intrinsic competencies[1013], we refrained from asking respondents to describe learning needs and challenges pertaining to these specific competencies. Rather, our aim was to elicit authentic descriptions of learning needs and challenges encountered in practice across a wide range of specialists.…”
Section: Methodsmentioning
confidence: 99%
“…Part of the reason for this focus may be related to a lack of clarity regarding such personal and professional competences. Indeed, researches in academic settings have found that physicians do not fully understand the basic constructs underlying intrinsic competencies [1013]. For example, faculty members often avoid assessing intrinsic CanMEDS roles, particularly those related to collaborator, leader, health advocate, and scholar, which suggests that individuals may not understand the constructs underlying such roles [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, assessment practices and standards shape how learners come to think about their practice and how to continually improve it. However, the work conducted by Renting et al 1 shows a lack of integration of the language of the competency framework into daily learning interactions: where 'the names of CanMEDS roles were rarely mentioned outside formal assessment situations'. Therefore, at least in this case, the standards may not be leading to greater transparency of expectations in the day-to-day learning environment for either the trainees or their supervisors.…”
Section: Cost-effectiveness Analysis Is Relatively Uncommon In Medicamentioning
confidence: 99%
“…In this issue of Medical Education , Renting et al . present an interesting study exploring how CanMEDS roles are ‘given expression in a clinical workplace’ using communities of practice theory.…”
mentioning
confidence: 99%